Research recast(ed): S2E13 - Mating, romance, and cannibalism in the insect world with Dr. Kevin Judge - Miskiman, Megan; Schabert, Reinette; Judge, Kevin (My University, 2023)
In today’s episode, associate professor of the Biology Department here at MacEwan, Dr. Kevin Judge, discusses his research on the sexual selection and mating system of insects part of the genus, Cyphoderris.
Keywords: Cyphoderris; insects; sexual selection; mating